Characteristics Of Fatigue Post Stroke Patient’s - Mohammad Arifin Noor (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2018)
Introduction: Fatigue in stroke patients can occur during the acute phase (2 weeks) or for a long time after the attack. This study aimed to find out the description of fatigue characteristics of post stroke patients. Descriptive analytical methodology with cross sectional design, 22 people (sample) obtained by purposive sampling technique. The research sample is stroke patient with fatigue. The results of the frequency distribution test showed the average age of respondents 54.68 ± 8.00 with 95% CI 48.90-61.65, female gender (63.6%), mild-moderate emotional disturbance (59.1%) , average post-stroke fatigue score 38.87 ± 7.83 and 95% CI 35.71 - 42.66. Discussion: the characteristics of patients experiencing fatigue is very diverse, it is necessary to see the correlation between characteristics with the incidence of fatigue post stroke